THE IMPACT OF CREATIVE PROBLEM SOLVING MODEL ON STUDENT LEARNING OUTCOMES IN INFORMATION AND COMMUNICATION TECHNOLOGY: A CASE STUDY AT PUBLIC JUNIOR HIGH SCHOOL N 7 AMABI OEFETO TIMUR - Sarlota Uriana Babu; Ellen Tantrisna; Roswita Lioba Nahak (Universitas Citra Bangsa, 2024)
This study aims to determine whether the implementation of the Creative Problem Solving (CPS) model has an effect on student learning outcomes in Information and Communication Technology (ICT) with study case at Public Junior High School N 7 Amabi Oefeto Timur. The methodology consisted in a quasi-experimental design study through the comparison of results under the pedagogy model CPS, taught to an experimental group and on traditional education, implemented on control group. Results showed that the experimental group had higher post-test scores than the control group in higher order thinking skills (problem-solving abilities) and understanding of ICT concepts. This was additionally seen with classroom observations where the students in the experimental group presented greater involvement, confidence in applying concepts of ICT to practical issues and collaboration with the peers. The first thing the CPS model did was start teaching students to think critically, accept that there are always multiple solutions and that together they can solve the problem. The findings indicated that the CPS model is an appropriate pedagogy for enhancing ICT learning performance, especially in resource-poor school contexts. The study suggests that the CPS model should be more prevalent in ICT education and should also be applied in online learning settings.